2009
DOI: 10.1111/j.1365-2869.2008.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

A combined neuropsychological and brain imaging study of obstructive sleep apnea

Abstract: SUMMARY Patients with obstructive sleep apnea (OSA) show neuropsychological impairments ranging from vigilance decrements, attentional lapses and memory gaps to decreased motor coordination, but their cognitive profile, and the origin of the impairments, remain unclear. We sought to establish the neuropsychological profile of 16 newly diagnosed apneics and to highlight both their morphological and functional brain abnormalities. We used an extensive neuropsychological test battery to investigate attention and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

26
193
4
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 215 publications
(235 citation statements)
references
References 74 publications
26
193
4
12
Order By: Relevance
“…6,7,14,[16][17][18] Weaknesses in motor dexterity have also been reported in children with snoring or OSAS and adults with OSAS. 24,43,44 The present results offer support for small effects of treatment in these same domains. The effects of sleep disturbance on cognition and behavior have been attributed to sleepiness and to adverse effects of intermittent hypoxia and sleep fragmentation on neural development and brain functioning.…”
supporting
confidence: 69%
“…6,7,14,[16][17][18] Weaknesses in motor dexterity have also been reported in children with snoring or OSAS and adults with OSAS. 24,43,44 The present results offer support for small effects of treatment in these same domains. The effects of sleep disturbance on cognition and behavior have been attributed to sleepiness and to adverse effects of intermittent hypoxia and sleep fragmentation on neural development and brain functioning.…”
supporting
confidence: 69%
“…Although the authors did observe only little deficits in the functions assessed (mainly memory and motor function), functional brain changes could be detected, suggesting that such modifications precede the clinical manifestations 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating cognitive performance in patients with OSA have been able to distinguish the impairment resulting from EDS from that determined by chronic obstructive pulmonary disease, which traditionally assumes the occurrence of ischemic prefrontal lesions [21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…An early study assessing changes in patients with OSA reported diffuse changes in the frontal, temporal and parietal cortices, as well as in the anterior cingulate gyrus, hippocampus, and cerebellum (67). Subsequently, a combined VBM and PET imaging study demonstrated hypotrophic changes in wider circuitry, as well as a decrease in cortical metabolism despite no clinically overt cognitive deficits being present (64). This has been argued to suggest early processes likely leading to later clinically measurable cognitive changes.…”
Section: Neuroanatomy Of Osamentioning
confidence: 99%
“…Historically, a number of voxel based morphometry (VBM) studies have investigated areas of the brain affected in patients with OSA with diverse regions being highlighted as more or less impacted (62)(63)(64)(65)(66). An early study assessing changes in patients with OSA reported diffuse changes in the frontal, temporal and parietal cortices, as well as in the anterior cingulate gyrus, hippocampus, and cerebellum (67).…”
Section: Neuroanatomy Of Osamentioning
confidence: 99%